Analisis Hukum Islam dan Undang-Undang Perkawinan terhadap Istri yang menolak Hubungan Intim - Rifky, Sehan; Saepullah, Asep; Maolia, Nadia Cahya (Jurnal Keislaman, 2024)
In marriage, both husband and wife are required to carry out the rights and obligations, including the rights and obligations in intimate relationships. Islamic law and the Marriage Law regulate all aspects of married life. The aim of this research is to analyze the provisions of wives who reject intimate relations from the perspective of Islamic law and marriage law. The methodology used in this research uses qualitative research with literature study research procedures and uses deductive data analysis methods. So the research results were obtained, namely the first analysis of Islamic law, wives are required to continue to have the obligation to serve/serve their husbands, wherever and whenever with all their body and soul and an open heart. If the wife refuses, then the wife will have no blessings in her life and will be disobedient to her husband, except when the wife has obstacles that are justified by the Shari'a, such as illness, menstruation and childbirth. The second analysis of the Marriage Law in article 31 number 1 of 1974 confirms that the position and rights of the wife are the same as the position and rights of the husband in married life and in interacting with each other and with society, including the position and rights in intimate relations, husband or wife. has the right to refuse invitations to have intimate relations, reinforced by article 33 which states that husband and wife are obliged to care for each other, love, have and respect each other, be loyal and provide physical and spiritual assistance to each other, so between Islamic law and the marriage law There is a common thread that can be taken away, namely that there must be good communication between husband or wife in the context of intimate relationships and a strong sense of tolerance must be fostered so that a sakinah mawadah warahmah household can be built.